Assessing knowledge and skills of maternity care professionals regarding neonatal hyperbilirubinaemia: a nationwide survey - Berthe A. M. van der Geest; Imke M. Theeuwen; Irwin K. M. Reiss; Eric A. P. Steegers; Jasper V. Been (BMC, 2021)
Abstract Background Neonatal hyperbilirubinaemia is a physiologic phenomenon, but, when severe, may cause lifelong disability. Maternity care assistants (MCAs) play an important role in timely recognition of severe neonatal jaundice. We assessed knowledge and skills of MCAs regarding neonatal hyperbilirubinaemia. Methods All Dutch MCAs (n = 9065) were invited to fill out a questionnaire assessing knowledge, expertise, and handling of neonatal jaundice. Additionally, we developed an e-learning and provided training sessions to a subgroup of MCAs (n = 99), and assessed their knowledge on neonatal hyperbilirubinaemia before and after the training. Results One thousand four hundred sixty-five unique online questionnaires were completed (response 16.2%). The median number of correctly answered knowledge questions was 5 (out of six; IQR 1). Knowledge was significantly better when respondents had had in-service training on neonatal hyperbilirubinaemia in the previous year (p = 0.024). Although 82% of respondents felt highly skilled or skilled to assess jaundice, accuracy of estimation of total serum bilirubin levels by assessing skin colour was generally poor and prone to underestimation. Among participants attending a training session, those who completed the e-learning beforehand had higher pre-training scores (5 (IQR 1) vs. 4 (IQR 2); p < 0.001). The median post-training score was higher than pre-training (6 (IQR 1) vs. 5 (IQR 2); p < 0.001). Conclusions Background knowledge of MCAs regarding neonatal hyperbilirubinaemia was adequate, but can be improved by further training. Estimation of total serum bilirubin levels based on skin colour was often inadequate. Approaches to improve timely recognition of jaundiced neonates are needed.